Produtividade e resposta de progênies de Coffea arabica L. a colheita semi-mecanizada - Dias, Rodrigo Elias Batista Almeida (2016)
The use of more productive Coffea arabica L. cultivars, with attributes favorable to semi-mechanized harvest, is very important for expanding coffee production. With this work, we aimed at selecting Coffea arabica cultivars, aiming for semimechanized harvest. The experiment was installed in January of 2007, in the Experimental Fields belonging to EPAMIG, in the municipalities of Machado and São Sebastião do Paraíso, both in Minas Gerais, Brazil. The 2014 and 2015 harvests were used to evaluate the following parameters: natural fall of fruits, productivity, defoliation, plant vigor, percentage of fruit maturation, fruit detachment strength and determination of harvest efficiency. We evaluated adaptability and stability of progenies from the years of 2009 to 2015, as well as the agronomic characteristics related to yield: income determination, yield and sieve analysis. The experimental design used was in randomized blocks, with four replicates and plots constituted of 10 plants. The statistical analyses of the data were conducted by using the R software®, version 3.2.1 (2015). Progeny F (H 105-01 -39 Cova 1) presented good productivity and high seed dropping efficiency, high confidence indexes and favorable characteristics for semimechanization, allowing the use for generation advancement in the coffee breeding program.